Water motion and pH jointly impact the availability of dissolved inorganic carbon to macroalgae - Rebecca K. James; Christopher D. Hepburn; Daniel Pritchard; Derek K. Richards; Catriona L. Hurd (Scientific Reports, 2022)
Abstract The supply of dissolved inorganic carbon to seaweeds is a key factor regulating photosynthesis. Thinner diffusive boundary layers at the seaweed surface or greater seawater carbon dioxide (CO2) concentrations increase CO2 supply to the seaweed surface. This may benefit seaweeds by alleviating carbon limitation either via an increased supply of CO2 that is taken up by passive diffusion, or via the down-regulation of active carbon concentrating mechanisms (CCMs) that enable the utilization of the abundant ion bicarbonate (HCO3 −). Laboratory experiments showed that a 5 times increase in water motion increases DIC uptake efficiency in both a non-CCM (Hymenena palmata, Rhodophyta) and CCM (Xiphophora gladiata, Phaeophyceae) seaweed. In a field survey, brown and green seaweeds with active-CCMs maintained their CCM activity under diverse conditions of water motion. Whereas red seaweeds exhibited flexible photosynthetic rates depending on CO2 availability, and species switched from a non-CCM strategy in wave-exposed sites to an active-CCM strategy in sheltered sites where mass transfer of CO2 would be reduced. 97–99% of the seaweed assemblages at both wave-sheltered and exposed sites consisted of active-CCM species. Variable sensitivities to external CO2 would drive different responses to increasing CO2 availability, although dominance of the CCM-strategy suggests this will have minimal impact within shallow seaweed assemblages.